Search for the associated production of the Higgs boson with a top-quark pair - (:unkn) unknown (SPRINGER, 2014)
A search for the standard model Higgs boson produced in association with a top-quark pair (t (t) over barH) is presented, using data samples corresponding to integrated luminosities of up to 5.1 fb(-1) and 19.7 fb(-1) collected in pp collisions at center-of-mass energies of 7 TeV and 8 TeV respectively. The search is based on the following signatures of the Higgs boson decay: H -> hadrons, H -> photons, and H -> leptons. The results are characterized by an observed t (t) over barH signal strength relative to the standard model cross section, mu = sigma/sigma(SM), under the assumption that the Higgs boson decays as expected in the standard model. The best fit value is mu = 2.8 +/- 1.0 for a Higgs boson mass of 125.6 GeV.
Keywords: Hadron-Hadron Scattering; Higgs physics; Top physics; BROKEN SYMMETRIES; BREAKING; NLO